Menopause in women with polycystic ovary syndrome - Grzechocińska, Barbara (Menopause Review/Przegląd Menopauzalny, 2005)
There are many factors influencing health condition in menopausal women. It seems that one of those factors is hormonal status in premenopausal period. There are not many studies considering menopause in polycystic ovary syndrome women although relatively high prevalence of PCOS in women of reproductive age (5-7%). The reasons are disagreements in diagnostic criteria and too small study population in epidemiological studies making unable to compare the outcomes. A number of studies have shown the risk of developing diabetes, cardiovascular disease, hypertension and obesity during menopause in PCOS women. There is an association between PCOS and endometrial cancer and may be an increased risk of breast carcinoma. An association between PCOS and ovarian cancer in unlikely. Many authors suggest that hormonal therapy, treating insuline resistence, hyperandrogenism and obesity might have long term beneficial sequelae. Although the degree of risk in treated and untreated women has not been yet clearly defined. Further clinical and epidemiological studies of this problem are required.